The agro-enterprise appproach increases incomes for Tanzanian smallholder farmers - Mbele, Savior (Technical Centre for Agricultural and Rural Cooperation, 2018)
To reduce poverty and increase food security for smallholder paddy farmers in Tanzania, the national government started the Marketing, Infrastructure, Value Addition and Rural Finance programme. The programme uses the Public, Private Producer Partnership approach to bring together different actors to reduce transaction costs along the value chain, and puts paddy farmers in direct contact with potential buyers.